Partially adaptive baeam-forming maethods based on genetic algorithms - JIN Jun1; WANG Hua-li1; LIU Miao2 (Tongxin xuebao)
An improved genetic algorithm（GA） for real time beam-forming of onboard planar array was presented. In or-der to meet the real-time processing requirements, this GA was combined with partially adaptive beam-forming tech-niques in the phase-only adaptive array, which can decrease the calculation complexity, and speed up its convergence rates. Two partially adaptive schemes, partial elements and partial bits adaptive beam-forming, were discussed with the genetic algorithm. The computer simulations show that the above two methods can null interferences located on the sidelobe regions, while the mainlobe can keep the satisfying gain levels at the angle of beam-pointing. Moreover, they offer the advantage of faster convergence rates over phase-only algorithm.